Cyclobutane-substituted diacetamido sulfides and 2,5-diacylthiophenes - Koparir, M; Cansiz, A; Ahmedzade, M; Çetin, A (John Wiley & Sons Inc, 2004)
A general and convenient route for the synthesis of 2,5-di[1-methyl-1-arylcyclobutane-3-yl]-thiophenes 4a-c and bis[1-methyl-1-arylcyclobutane3-yl]-2-(2-oxyethtylamido)thiazole sulfides 7a-c is reported. The characterization of these compounds was obtained by elemental analyses, IR, C-13, and H-1 NMR techniques. (C) 2003 Wiley Periodicals, Inc.